A Novel c-MET-Targeting Antibody-Drug Conjugate for Pancreatic Cancer - Jin, Yangbing; Zhang, Zehui; Zou, Siyi; Li, Fanlu; Chen, Hao; Peng, Chenghong; Deng, Xiaxing; Wen, Chenlei; Shen, Baiyong; Zhan, Qian (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer-associated death in the United States and has a 5-year survival rate of less than 4%. Although much effort has been invested in the research and development of pancreatic cancer drugs over the past 30 years, due to the lack of effective targetable carcinogenic drivers, no new targeted therapies that can improve patient prognosis have been approved for clinical use. SHR-A1403 is a new c-mesenchymal-epithelial transition factor (c-MET) antibody-drug conjugate (ADC) that can be used for the targeted treatment of PDAC with high expression of c-MET. This study reported for the first time the application prospects of SHR-A1403 in preclinical models of PDAC. SHR-A1403 significantly inhibited the proliferation, migration, and invasion of pancreatic cancer cells and induced cell cycle arrest and apoptosis. These changes were caused by inhibition of intracellular cholesterol biosynthesis by SHR-A1403. Therefore, targeting c-Met through SHR-A1403 showed strong preclinical anti-tumour efficacy in pancreatic cancer. Our work suggests the potential application of c-MET-targeted ADC treatment for PDAC in clinical practice.